Understanding Artificial Intelligence: What It Is and How It Is Used in Agriculture: AE589, 10/2023 - Choi, Daeun; Mirbod, Omeed; Ilodibe, Uchechukwu; Kinsey, Steven (EDIS, 2023)
The primary goal of this article is to provide background knowledge and terms that frequently come up in other articles about AI as well as in general use. The target audiences of this series include the general public, Extension educators, and farmers who want to know more about AI systems and their applications. This series will help readers understand the opportunities that AI brings to agriculture as smart technologies continue to grow in the market. Written by Daeun Choi, Omeed Mirbod, Uchechukwu Ilodibe, and Steven Kinsey, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2023.